Implementation of Law Number 6 of 2014 concerning the Election of Village Heads in Cinta Damai Village, Percut Sei Tuan District, Deli Serdang Re-gency in 2022 from the Perspective of Siyasah Dusturiyah - Masriadji, Fajar; Fatimah, Fatimah (LEGAL BRIEF, 2025)
This study aims to examine the implementation of Law Number 6 of 2014 concerning Village Head Elections in Cinta Damai Village, Percut Sei Tuan District, Deli Serdang Regency in 2022 from a Siyasah Dusturiyah perspective. Village head elections are a concrete form of local democracy that provides space for village community participation in determining leaders. However, in practice, elections in Cinta Damai Village were marred by alleged violations of election principles, such as voters whose domiciles do not match their ID cards, voters who were replaced by other parties, and negligence by the committee in verifying voter data. The Siyasah Dusturiyah perspective assesses that these actions violate the principles of justice, trustworthiness, and honesty, which are the main foundations of Islamic law. The research method used is an empirical legal approach with data collection through interviews and observations. The findings indicate weak supervision and implementation that is not in accordance with democratic principles and sharia values, resulting in conflict and community dissatisfaction. Therefore, system improvements and strict supervision are needed in the implementation of the Village Head Election to comply with positive legal provisions and the principles of justice in Islam